Covid-19, Human Displacement, and Expanding Crises of Insecurity in Africa: The case of Almajiri Children in Nigeria - Agunyai, Samuel Chukwudi; Ojakorotu, Victor (International Journal of Criminology and Sociology, 2021)
Governance failures, inadequate policy efforts, poverty, unemployment, insurgency, climate change, socio-economic downturns, religious fanatics or bandits, and other related factors have all been blamed for insecurity in Africa. This has left some holes in assessing Africa’s present catastrophic insecurity situation via the prism of Covid-19 and human displacement. The research fills the gaps by presenting a fresh understanding of how Covid-19 and the illogical displacement of Almajiri children play a role in Nigeria’s recent rise in instability. It makes considerable use of secondary sources and reviews empirical works on the issue. The results demonstrated that the Covid-19 shutdown sparked more banditry. Almajiri children were exposed to rebels and bandits who used them to carry out dangerous attacks on the Nigerian state. The breakout of Covid-19, according to results, partly contributed to the increase in insecurity in Nigeria.